Cybaeus (Araneae: Cybaeidae): the Nearctic species of the Holarctic clade - Bennett, Robb; Copley, Claudia; Copley, Darren (Zootaxa, 2016)
Species of North American Cybaeus L. Koch (Araneae: Dictynoidea: Cybaeidae) are classified in Holarctic and Californian clades. We review the Nearctic species of the Holarctic clade of these common moist-forest spiders. Twenty-one species grouped in informal tetricus (nine species) and angustiarum (twelve species) groups based on female genitalic characters are recognized, including four new species endemic to the western Nearctic: C. rothi Bennett sp. nov. (tetricus group) and C. charlesi Bennett sp. nov., C. harrietae Bennett sp. nov., and C. solanum Bennett sp. nov. (angustiarum group). Other Nearctic species in the tetricus group are C. cascadius Roth 1952, C. conservans Chamberlin & Ivie 1932, C. constrictus Chamberlin & Ivie 1942, C. eutypus Chamberlin & Ivie 1932, C. morosus Simon 1886, C. multnoma Chamberlin & Ivie 1942, C. paralypropriapus Bennett 2009, and C. waynei Bennett 2009. Other Nearctic species in the angustiarum group are C. bulbosus Exline 1935, C. giganteus Banks 1892, C. patritus Bishop & Crosby 1926, C. reticulatus Simon 1886, C. scopulatus Chamberlin & Ivie 1942, C. shoshoneus Chamberlin & Ivie 1932, C. signifer Simon 1886, C. silicis Barrows 1919, and C. sinuosus Fox 1937. Approximately half of the Nearctic Cybaeus species of the Holarctic clade are relatively widely distributed and frequently encountered; the remaining species have restricted ranges. Descriptions, illustrations, and range maps are provided for all species and identification keys are also included.